Rapid Formation of Kinetically Sprayed Cu-Sn Intermetallic Film. (21st October 2019) - Choi, Dahyun; Kang, Suhee; Kim, Hyungsub; Kim, Hyojun; Lee, Caroline Sunyong
Abstract : The kinetically spraying method was used to fabricate an in situ copper- (Cu-) tin (Sn) intermetallic compound (IMC) film with its thickness of approximately 1 μ m using a Cu-Sn mixed powder. Microsized Cu ( 5 μ m) and Sn ( 10 μ m) powders were mixed at its ratio of 45 : 55 wt.%, respectively, and then deposited onto a silicon substrate, forming an IMC layer. The actual composition of the deposited film was measured to be at a Cu : Sn ratio of 36 : 64 wt.% (in situ kinetically sprayed at 200°C). This kinetically sprayed process uses the energy source of collision and heat energy simultaneously, leading to the formation of an IMC phase. The IMC phase of Cu6 Sn5 was formed successfully within 3 minutes of in situ deposition. Moreover, we obtained a Cu6 Sn5 phase when the thin film was annealed in a furnace for 1 hour immediately after kinetically spraying at room temperature. However, an IMC phase was not formed in the thin film when kinetically sprayed at room temperature followed by heating on a hot plate for 3 minutes. It seems that the simultaneous supply of collision and heat energy is crucial to result in phase formation. Therefore, we have proven that the kinetically spraying process is capable of fabricating a super-thin layer of IMC film within a short time.